Conférences internationales - Trébuchon, Jean-François (BOIS & FORETS DES TROPIQUES, 2023)
The “7th European Conference of Tropical Ecology”, which is also the “35th Annual Meeting of the Society for Tropical Ecology” (Gesellschaft für Tropenökologie, gtö), in 2024 will be hosted by the University of Lisbon, from 12th to 16th of February 2024. The overarching topic will be “Tropical ecosystems in a fast-changing planet”. It will provide an interdisciplinary platform for discussing major advances, challenges, and future opportunities in tropical ecology. Chairs : Jorge Palmeirim, University of Lisbon, Portugal https://ce3c.ciencias.ulisboa.pt/member/jorge-palmeirim Site web : https://www.soctropecol-conference.eu/